Phytochemical analysis of high value medicinal plant Valeriana jatamansi using LC-MS and it's in-vitro anti-proliferative screening - Vijaya Shukla; Pratibha Singh; Deepak kumar; Rituraj Konwar; Bikarma Singh; Brijesh Kumar (Elsevier, 2021)
Background: Phytochemicals are group of compounds derived from plant resource and shown to have many pharmacological activities. Identification and quantification of chemical constituents in complex matrix of plant is a challenging task. LC-MS is the most prominent analytical technique for this purpose. Purpose: The aim of the present study is identification and quantification of bioactive compounds from Valeriana jatamansi using LC-MS and their in-vitro anti-proliferative screening. Materials and Methods: HPLC-ESI-QTOF-MS/MS separation for qualitative analysis was performed with the aid of an Agilent Poroshell 120 ECC18 column (2.7 μm, 50 mm × 4.6 mm). For quantitative analysis UPLC-ESI-QqQLIT−MS/MS separation was achieved on ACQUITY UPLC BEH™ C18 column (1.7 μm, 50 mm × 2.1 mm). The eluents were water with 0.1% formic acid (A) and acetonitrile (B). The anti-proliferative activity of samples of V. jatamansi on exponentially growing breast cancer cells was determined by the sulphorhodamine B (SRB) assay. Results: An efficient and sensitive LC-MS method was developed for metabolite profiling of five samples of V. jatamansi which resulted in the identification of forty-seven compounds by HPLC-ESI-QTOF-MS/MS. Nine bioactive compounds were quantified for the first time in leaves and roots of V. jatamansi using UPLC-ESI-QqQLIT−MS/MS. Quantitation method was also validated according to ICH guidelines. The correlation coefficient values (r2> 0.9873), LODs and LOQs for each analyte were < 15.7 and 47.6 ng/mL. The intra and inter-day precision variations (RSD) are <2.30 and 2.49%, respectively. Stability of the analytes is ≤ 1.85%. The average recovery was in the range 96.48-109.49% with RSD from 0.95 to 2.41%. Conclusion: Phytochemical analysis of extracts followed by biological activity was successfully completed to ensure safety and efficacy. Content of marker compound valerenic acid was found higher in samples collected from Patnitop (VJPL) (0.38 mg/g) and Sanasar (VJSL) (0.27 mg/g). These samples (VJPL and VJSL) also showed lowest IC50; hence, more effective on breast cancer cell lines (MCF-7 and MDA-MB-231).